INTERRELATIONSHIPS BETWEEN YIELD AND YIELD COMPONENTS IN FOXTAIL MILLET [ AIL MILLET [Setaria italica Setaria italica (L.) Beauv .) Beauv.] GENOTYPES GENOTYPES - SATISH KUMAR SINGH S. K. VARSHNEY AND A. K. SINGH (The Bioscan, 2018)
Thirty four genotypes of foxtail millet evaluated for correlation and path coefficient analysis at research farm of Tirhut College of Agriculture, Dr. Rajendra Prasad Central Agricultural University, Pusa, Bihar. Data were recorded for twelve quantitative characters, viz., plant height, days to flowering, number of basal tillers per plant, flag leaf blade length, flag leaf blade width, flag leaf sheath length, peduncle length, panicle exertion, inflorescence length, inflorescence width, weight of five panicles, yield per plot, yield per hectare. Correlation studies indicated that positive correlation was observed for weight of five panicles, inflorescence length, inflorescence width, flag leaf sheath length, flag leaf blade length, flag leaf blade width, number of basal tillers, plant height and days to fifty per cent flowering with yield per hectare and out of these inflorescence length (0.2199*), inflorescence width (0.5270**) and weight of five panicles (0.7172**) showed significant values. However, the association of peduncle length (-0.3691**) and panicle exertion (-0.3665**) with yield per hectare was negative, simultaneous improvement of yield along with these traits is not possible. The path analysis study indicated that direct selection based on the characters, weight of five panicles and number of basal tiller are effective as their association and direct effects were positive.